Smoking Behavior In Indonesian Society - Henik Tri Rahayu; Amelinda Nur Kartika Rachmah (International Journal Labs, 2025)
Introduction: Smoking is a global health threat, with 22.3% of the world's population using tobacco in 2020, dominated by 36.7% men and a small proportion 7.8% women. More than 80% of global smokers are in low-middle-income countries, including Indonesia in 2007 which in 2007 ranked as the 5th most smoker in the world. Objective: to describe people's smoking patterns by gender, as well as describe demographic characteristics, smoking risk factors, and types of cigarettes in Indonesia using DHS 2017 data. Methods: This study used a cross-sectional quantitative research design with secondary data from DHS 2017. Data were analyzed using SPSS version 23. The Chi-Square test was used to identify differences in the proportion of independent variables by gender, with a significance level of ?=0.05. Results: there was a significant difference between males and females in the demographic distribution (p < 0.001). While the majority of both sexes were non-smokers, there were significant differences in smoking status (p < 0.001) and smoking frequency (p < 0.001), with a higher proportion of female smokers (3.7%) than men (2.2%). The prevalence of cigarette use (p < 0.001) and inhaled through nose (p = 0.010) showed a significant association with sex, although the absolute prevalence was low. Conclusion: there is a relationship between sex and demographic characteristics, smoking risk factors, and types of cigarettes. So that the prevention and control of smoking in Indonesia can consider demographic and gender profiles, focus on conventional cigarettes, and pay attention to differences in tobacco use tendencies